Superhydrophobic Polymeric Hollow Fiber Membrane Contactors For CO2 Absorption - Mohammed, Harith Noori (2014)
In recent years the climate change became a global concern due to the increasing of the earth’s surface temperature. This phenomenon was exacerbated by the expansion of industrial activities due to the increasing emissions of the greenhouse gas (mainly CO2). Dalam beberapa tahun ini perubahan cuaca telah menjadi masalah global disebabkan kenaikan suhu permukaan bumi. Fenomena ini menjadi semakin teruk akibat aktiviti-aktiviti industri disebabkan kenaikan pengeluaran gas rumah hijau (terutamanya CO2).